Efficacy and safety of the Ayurvedic herbal preparation Maharishi Amrit Kalash: a systematic review of randomized controlled trials - Koch, Anna K.; Patel, Manish; Gupta, Shivenarain; Wullenkord, Ricarda; Jeitler, Michael; Kessler, Christian S. (Frontiers in Medicine, 2024)
Background: Maharishi Amrit Kalash (MAK) 4 and 5 are Ayurvedic herbal nutritional supplements that are believed to have beneficial effects on overall health and well-being. This study's aim is to systematically review all available randomized controlled trials (RCTs) investigating clinical effects and safety of MAK.We included RCTs on therapy, health promotion, and prevention for patients and healthy volunteers of all ages. We systematically searched MEDLINE (via PubMed), EMBASE (via Ovid), the Cochrane Central Register of Controlled Trials (CENTRAL, The Cochrane Library), DHARA, Clinicaltrials.gov, the World Health Organization (WHO) International Clinical Trials Registry Platform, and Google scholar from inception through May 7 th , 2023, with no time or language restrictions. Risk of bias was assessed using the Cochrane Risk of Bias Tool version 1. The protocol was registered with PROSPERO before conducting the review (CRD42023421655).Results: Three RCTs with 418 study participants were included. Two studies were on breast cancer patients and one on healthy adults. The two studies on cancer evaluated the efficacy of MAK in reducing side effects of chemotherapy in women with breast cancer. The study on healthy adults evaluated whether MAK has an effect on an age-related alertness task as an indicator of cognitive aging. Both studies on breast cancer patients found beneficial effects on performance status, anorexia, vomiting, and body weight. One study reported positive effects regarding stomatitis. Regarding visual alertness, results showed that individuals who received MAK improved in performance. None of the three included studies reported adverse events. Risk of bias was mixed. Due to the small amount and heterogeneity of the RCTs, no meta-analysis could be performed.There is evidence that MAK may have supportive effects in chemotherapeutic treatments for breast cancer patients and for healthy individuals regarding visual discrimination. However, it is difficult to verify treatment effects due to the small number of RCTs and the mixed risk of bias. Also, none of the included studies recorded adverse events. Therefore, further highquality studies are warranted to confirm the potential health benefits of MAK and to determine its optimal dosage and duration of use.